2007
DOI: 10.1111/j.1468-1293.2007.00463.x
|View full text |Cite
|
Sign up to set email alerts
|

Performance of a World Health Organization first‐line regimen (stavudine/lamivudine/nevirapine) in antiretroviral‐naïve individuals in a Western setting

Abstract: ObjectivesIn 2003, the World Health Organization (WHO) and Joint United Nations Programme on HIV/AIDS (UNAIDS) introduced the '3 by 5 Initiative' to treat 3 million individuals by the end of 2005. This study evaluates the time to treatment termination, viral load suppression, and detection of drug resistance among antiretroviral-naïve individuals initiating stavudine/lamivudine/nevirapine (d4T/3TC/NVP) in British Columbia, Canada, to provide a context for future programme planning. MethodsPrimary outcome was t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 9 publications
1
8
0
Order By: Relevance
“…An early study from Senegal showed that 12.5% had one or more drug resistance mutations after a median of 30 months on ART [26], whereas a recent study from Côte d'Ivoire found 22% resistance after a median of 37 months on ART [27]. These results should not be used as an argument against HIV treatment in Africa; in fact, the results are comparable to a recent study from Canada, where 20% developed resistance after 30 months on the ART regimen most widely used in resource-limited settings (stavudine/lamivudine/nevirapine) [28]. Thus, emergence of drug resistance appears to occur at a similar rate in Africa as in a Western setting.…”
Section: Discussionmentioning
confidence: 83%
“…An early study from Senegal showed that 12.5% had one or more drug resistance mutations after a median of 30 months on ART [26], whereas a recent study from Côte d'Ivoire found 22% resistance after a median of 37 months on ART [27]. These results should not be used as an argument against HIV treatment in Africa; in fact, the results are comparable to a recent study from Canada, where 20% developed resistance after 30 months on the ART regimen most widely used in resource-limited settings (stavudine/lamivudine/nevirapine) [28]. Thus, emergence of drug resistance appears to occur at a similar rate in Africa as in a Western setting.…”
Section: Discussionmentioning
confidence: 83%
“…In a recent analysis, an appreciable percentage of patients accumulated drug resistance or required second-line treatment relatively soon after the start of first-line ART with stavudine, lamivudine, and nevirapine [3]. Similar studies of patients receiving first-line ART in Africa and Thailand showed a high rate of TAM accumulation in patients with immunological or clinical failure in response to WHO-recommended treatments [4][5][6][7][8][9][10][11].…”
mentioning
confidence: 96%
“…29-31 With the evolving HIV-1 epidemic in China, it becomes necessary to monitor HIV-1 resistant variants to antiretroviral agents in newly infected individuals. 27, 32, 33 …”
Section: Discussionmentioning
confidence: 99%